Simulation-based ENT induction: validation of a novel mannequin training model. Issue 1 (23rd January 2020) - Bhalla, S; Beegun, I; Awad, Z; Tolley, N
Abstract: Objective: To ascertain whether simulation-based teaching is superior to lecture-based teaching for an induction programme using a home-made induction model. Methods: A simulation-based induction programme was designed and separate lecture-based teaching covering the same content was organised for junior doctors. The junior doctors were asked to complete pre- and post-induction surveys regarding confidence and anxiety levels. The skills taught included microsuction, flexible nasendoscopy, and anterior and posterior nasal packing. Structured interviews were conducted after the programme to gain qualitative data for analysis. The trainees' knowledge retention was compared using a standardised written assessment one month after the session. Results: Simulation-based teaching using the induction model was associated with a statistically significant increase in confidence levels and reduction in anxiety levels, and was associated with greater knowledge retention. Conclusion: A regular simulation induction programme should be introduced using the induction model, as it leads to better knowledge retention and increased confidence levels.